Venous thromboembolism after major gynecological cancer surgery: an analysis of cause and effect from the experience of a tertiary referral oncologic centre - Ray, M. D.; N., Premanand; Rajan, Saroj; Rai, Romey (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Patients undergoing extensive gynecological oncologic surgeries are at greater risk for developing deep vein thrombosis and pulmonary embolism than other oncological procedures. The anatomical confinement of vessels, lymphatics, and other structures in the restrictive pelvic space is contributory. We aimed to establish the etiopathogenesis of venous thromboembolism (VTE) with our practical experience. Methods: We present our experience from a tertiary referral oncologic centre in north India in patients with ovarian cancer undergoing cytoreductive surgery (CRS) with or without HIPEC, with a focus on the incidence and etiopathogenesis of deep venous thromboembolism (DVT), including anatomical barriers, restricted movement during surgical dissection, risk stratification and preventive measures. Results: Of 250 patients who underwent cytoreductive surgery (CRS) for ovarian cancer, 124 additionally underwent hyperthermic intraperitoneal chemotherapy (HIPEC). 20 (8%) patients were diagnosed with DVT within 30 days of surgery, and 3 (1.2%) were detected after 30 days. It is the most common significant postoperative morbidity. Conclusions: DVT is the most common postoperative complication in patients undergoing CRS+HIPEC for carcinoma ovary. Anatomical confinement, closed dependant spaces and more significant surgical trauma to pelvic vessels and lymphatics may be the leading cause. Detailed knowledge of anatomy and careful surgical dissection may prevent the development of DVT.